2004
DOI: 10.1073/pnas.0305755101
|View full text |Cite
|
Sign up to set email alerts
|

Secreted proNGF is a pathophysiological death-inducing ligand after adult CNS injury

Abstract: The unprocessed precursor of the neurotrophin nerve growth factor (NGF), proNGF, has been suggested to be a death-inducing ligand for the neurotrophin receptor p75. Whether proNGF is a true pathophysiological ligand that is secreted, binds p75, and activates cell death in vivo, however, has remained unknown. Here, we report that after brain injury, proNGF was induced and secreted in an active form capable of triggering apoptosis in culture. We further demonstrate that proNGF binds p75 in vivo and that disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
235
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(238 citation statements)
references
References 20 publications
(34 reference statements)
3
235
0
Order By: Relevance
“…Taken together, these findings suggest that high MW NGF species are abundant in the nervous system and may have their own biological activity. Some have suggested an apoptotic role for proNGF (Lee et al 2001;Beattie et al 2002;Harrington et al 2004;Pedraza et al 2005), though proNGF also has been shown to have neurotrophic activities Reinshagen et al 2000;Fahnestock et al 2004).…”
Section: Function Of Ngf and Nt-3 Protein Speciesmentioning
confidence: 99%
“…Taken together, these findings suggest that high MW NGF species are abundant in the nervous system and may have their own biological activity. Some have suggested an apoptotic role for proNGF (Lee et al 2001;Beattie et al 2002;Harrington et al 2004;Pedraza et al 2005), though proNGF also has been shown to have neurotrophic activities Reinshagen et al 2000;Fahnestock et al 2004).…”
Section: Function Of Ngf and Nt-3 Protein Speciesmentioning
confidence: 99%
“…Recent studies have shown that proneurotrophins binding to p75 mediates cell death after injury or neurodegenerative diseases such as Alzheimer's dementia (Harrington et al 2004;Peng et al 2004;Pedraza et al 2005;Volosin et al 2006). Pro-neurotrophins are produced and then cleaved by furin and other proteases to produce the mature neurotrophin (Lee et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Pro-neurotrophins are produced and then cleaved by furin and other proteases to produce the mature neurotrophin (Lee et al 2001). The precursor form of NGF, proNGF is responsible for inducing apoptotic death in particular cellular contexts (Lee et al 2001;Beattie et al 2002;Harrington et al 2004;Volosin et al 2006). Proneurotrophins, such as proNGF and proBDNF, preferentially interact with sortilin together with p75 to form a complex capable of activating an apoptotic cascade (Lee et al 2001;Nykjaer et al 2004;Teng et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For immunohistochemistry, sections were treated for 30 min in 0.1% H 2 O 2 /methanol at 20°C, and then blocked (5% serum of host of secondary antibody/5% nonfat dry milk/0.1% Triton X-100/PBS) and incubated with primary antibody overnight at 4°C. The primary antibodies used were: p75 NTR (extracellular domain-directed: R&D Systems, 1:1,000; intracellular domain-directed: Promega, 1:500), proNGF (prodomain-specific, 1:100; Harrington et al, 2004), sortilin (R&D, 1:400), SorCS2 (intracellular domain-directed: generated by immunizing rabbits against huSorCS2 aa 1138-1159, coupled to KLH, 1:300; or extracellular domain directed: R&D Systems, 1:100), CD140b (PDGFR-, eBioscience, 1:200), IB4 (preconjugated to biotin, Vector Laboratories, 1:300), activated caspase-3 (Cell Signaling Technology, 1:200), tyrosine hydroxylase (Millipore, 1:150), CD31 (BD, 1:100), CD41 (BD, 1:100), fibrin(ogen) (FITCconjugated, Dako, 1:250), CD68 (TRITC-conjugated, Serotec, 1:100), CD45 (BD,1:200), and Gr1 (BD,1:200). Biotinylated secondary antibodies were conjugated to ABC reagent and detected using the VIP Peroxidase Substrate kit (Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Using antisera specific to the prodomain of proNGF that detects proNGF but not mature NGF (Harrington et al, 2004), we tone in the adult (Donovan et al, 1995;Glebova and Ginty, 2005;Habecker et al, 2008). In the adult heart, mature NGF is secreted tonically by cardiac myocytes to modulate synaptic transmission by sympathetic neurons (Luther and Birren, 2006).…”
Section: Myocardial Ischemia Induces Expression Of Prongf and Its Recmentioning
confidence: 99%